On Reliability Approach to Identification of Probabilty Distributions of Two Statistically Dependent Objects - Yessayan, Aram O. (Mathematical Problems of Computer Science, 2021)
The identification of the distributions of two objects is an answer to the question whether r1-th and r2-th distributions occurred, or not on the first and the second objects, correspondingly. Haroutunian and Hakobyan solved the problem reliable identification of probability distributions for two independent objects. In this paper we present the solution of the problem of logarithmically asymptotically optimal identification of probability distributions for two statistically dependent objects.